Postharvest Storage Practices of Maize in Rift Valley and Lower Eastern Regions of Kenya: A Cross-Sectional Study - Peter Koskei; Christine C. Bii; Protus Musotsi; Simon Muturi Karanja (International Journal of Microbiology)
An assessment of local farmers’ knowledge, attitude, and practices on postharvest maize storage and management was carried out with a view of understanding its role in maize contamination with mycotoxins and postharvest losses in Rift Valley and Lower Eastern Regions of Kenya among 165 and 149 farmers, respectively. Differences between the two regions were analyzed using the Chi-square test, Fisher exact test, and two-sample t-test. The median quantity of maize harvested by farmers in the two regions after shelling was 585 kg. A median of 20 kg of maize was put aside as a result of rotting before shelling, and there was a significant mean difference in maize set aside as a result of rotting between the two regions (107.88 kg vs. 31.96 kg; t (306.25) = 5.707, P value <0.001). The quantity of discoloured and mouldy maize consumed ranged from 0 to 90 kg; 7 (2.2%) respondents consumed mouldy maize, 36 (11.5%) fed it to cows, and 19 (6.1%) fed it to poultry. A small percentage (3.5%) believed mouldy maize is safe for human consumption, 23.6% for animal consumption, while 15.0% considered it safe for brewing, with the differences between the two regions being statistically significant (P value <0.05). Nearly half of the respondents (48.4%) kept maize on cobs indoors, 47.1% left it in the field without covering, and 33.1% consumed and sold maize while still green, with more farmers from Lower Eastern practicing this. The results of the study suggest that there were poor postharvest practices and low awareness levels among maize farmers and that this can lead to postharvest losses due to Fusarium spp. infection and mycotoxin contamination that poses a threat to human and animal food safety. This calls for interventions on better postharvest practices.